The TRIPOD Statement: how to present the results of diagnostic and prognostic studies - I. P. Kolos; D. A. Anichkov; S. A. Boytsov (Столичная издательская компания, 2015)
The TRIPOD Statement aims to improve the transparency of the reporting of a prediction model study. This document describes the rationale; clarifies the meaning of each item; and discusses why transparent reporting is important, with a view to assessing risk of bias and clinical usefulness of the prediction model. To aid the editorial process and help peer reviewers and, ultimately, readers. The editorial board of "Rational Pharmacotherapy in Cardiology" hopes that the ability to publish TRIPOD will be useful to our authors, reviewers and readers.